Determination of ECoG Information Flow Activity Based on Granger Causality and Hilbert Transformation - Demirer, Rüştü Murat; Özerdem, Mehmet Sıraç; Bayrak, Coşkun; Mendi, Şekip Engin (Elsevier Ireland Ltd, Elsevıer House, Brookvale Plaza, East Park Shannon, Co, Clare, 00000, Ireland, 2013)
Analysis of directional information flow patterns among different regions of the brain is important for investigating the relation between ECoG (electrocorticographic) and mental activity. The objective is to study and evaluate the information flow activity at different frequencies in the primary motor cortex. We employed Granger causality for capturing the future state of the propagation path and direction between recording electrode sites on the cerebral cortex. A grid covered the right motor cortex completely due to its size (approx. 8 cm x 8 cm) but grid area extends to the surrounding cortex areas. During the experiment, a subject was asked to imagine performing two activities: movement of the left small finger and/or movement of the tongue. The time series of the electrical brain activity was recorded during these trials using an 8 x 8 (0.016-300 Hz band with) ECoG platinum electrode grid, which was placed on the contralateral (right) motor cortex. For detection of information flow activity and communication frequencies among the electrodes, we have proposed a method based on following steps: (i) calculation of analytical time series such as amplitude and phase difference acquired from Hilbert transformation, (ii) selection of frequency having highest interdependence for the electrode pairs for the concerned time series over a sliding window in which we assumed time series were stationary, (iii) calculation of Granger causality values for each pair with selected frequency. The information flow (causal influence) activity and communication frequencies between the electrodes in grid were determined and shown successfully. It is supposed that information flow activity and communication frequencies between the electrodes in the grid are approximately the same for the same pattern. The successful employment of Granger causality and Hilbert transformation for the detection of the propagation path and direction of each component of ECoG among different subcortex areas were capable of determining the information flow (causal influence) activity and communication frequencies between the populations of neurons successfully. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Brain Computer Interface; ECoG; Granger Causalit; Multi-dimensional Hilbert; Transformation; Directed Transfer-Function; Brain; Connectivity; Networks; EEG; Beyin Bilgisayar Arabirimi; Granger Nedensellik; Çok Boyutlu Hilbert; Transformasyon; Yönlendirilmiş Transfer Fonksiyonu; Beyin; Bağlantı; Ağlar